Book review: Plummer, Deborah M. (2017). Inspiring and Creative Ideas For Working with Children, How to Build Relationships and Enable Change. Jessica Kingsley Publishers, ISBN 978184956519 - Linda O'Neill (Scottish Journal of Residential Child Care)
At first look, from a children's services worker's perspective, this looks like a 'pick up and play' kind of book. It has a colourful illustrated cover with lots of child-style drawings and words — myriads of which I had when I worked in schools — that contain bite-sized activities any group worker can pick up, quickly read and deliver a fun and engaging activity for children. Close attention should be paid to the tagline 'How to Build Relationships and Enable Change' though, because this is the substance of this easy to read and digestible book.